Zasady stabilizacji i elastyczności socjalistycznego podatku rolniczego - Kozłowski, Zygmunt (Wydział Prawa i Administracji UAM, 1967)
In socialist economy agricultural tax must be characterized by a certain degree of stability on the one hand, and flexibility on the other. This paper is an attempt to formulate the principles of a tax policy in this field. The author maintains the necessity of a stable tax assessement for a long period, but at the same time considers that this assessment should be compatible with profit-making factors in agriculture. A change in tax assessment can follow, in long periods, in accordance with changes originating in profit making factors on farms in various regions and of various soils. Realization of the tax in individual years should be flexible. It should be subordinate to a policy of relative stabilization of a growing trend in agricultural yield. Stabilization of growth in this yield should be treated as a fiscal policy aim, whereas the yearly agricultural tax rate only as one of the means of realizing this aim. In addition to the tax relief the fiscal policy can — to make tax assessment more flexibile — take advantage of deferred as well as obligatory, anticipatory payments (in years of low or exceptionally high yield).
Principles of stabilization and flexibility of agricultural tax